PERAN LEMBAGA DOMPET DHUAFA RIAU DALAM PEMBERDAYAAN EKONOMI MASYARAKAT KOTA PEKANBARU - Putri Citra Setiawati (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This research is motivated by the role of community development actors, where the community development actor here is the Dompet Dhuafa Riau institution. With research entitled The Role of the Dompet Dhuafa Riau Institution in Community Economic Empowerment in Pekanbaru City. The problem of this research is the role of the Dompet Dhuafa Riau Institution in Community Economic Empowerment in Pekanbaru City. The focus of this research is the role of the Dompet Dhuafa Riau Institution in Economic Empowerment in Pekanbaru City in 2020-2022. The theory used in this research is the theory of the role of institutions according to Indra Bastian, namely the role of institutions as motivators, the role of institutions as communicators and the role of institutions as dynamists. The method used is a qualitative research method. Data collection techniques by means of observation, documentation and interviews. The results of the author's research found that the role of the Dompet Dhuafa Riau Institute in economic empowerment through empowerment in productive zakat and this activity must be further increased considering the number of poor people in Pekanbaru City. There are several things that need to be improved, namely proper guidance in managing zakat so that it becomes maximally productive, regular guidance, and clarifying short-term and long-term goals.